Costimulation of soil glycosidase activity and soil respiration by nitrogen addition - Ji Chen; Yiqi Luo; Jianwei Li; Xuhui Zhou; Junji Cao; Rui‐Wu Wang; Yunqiang Wang; Shelby Shelton; Zhao Jin; Laura M. Walker; Zhaozhong Feng; Shuli Niu; et al. (Global Change Biology, 2017)
Unprecedented levels of nitrogen (N) have been deposited in ecosystems over the past century, which is expected to have cascading effects on microbially mediated soil respiration ( SR ). Extracellular enzymes play critical roles on the degradation of soil organic matter, and measurements of their activities are potentially useful indicators of SR . The links between soil extracellular enzymatic activities ( EEA s) and SR under N addition, however, have not been established. We therefore conducted a meta‐analysis from 62 publications to synthesize the responses of soil EEA s and SR to elevated N. Nitrogen addition significantly increased glycosidase activity ( GA ) by 13.0%, α ‐1,4‐glucosidase ( AG ) by 19.6%, β ‐1,4‐glucosidase ( BG ) by 11.1%, β ‐1,4‐xylosidase ( BX ) by 21.9% and β ‐D‐cellobiosidase ( CBH ) by 12.6%. Increases in GA were more evident for long duration, high rate, organic and mixed N addition (combination of organic and inorganic N addition), as well as for studies from farmland. The response ratios ( RR s) of GA were positively correlated with the SR ‐ RR s, even when evaluated individually for AG , BG , BX and CBH . This positive correlation between GA ‐ RR and SR ‐ RR was maintained for most types of vegetation and soil as well as for different methods of N addition. Our results provide the first evidence that GA is linked to SR under N addition over a range of ecosystems and highlight the need for further studies on the response of other soil EEA s to various global change factors and their implications for ecosystem functions.